Synthesis and properties of some pyrazole derivatives of 1,2,4-triazole-3-thiol - Hotsulia, A. S.; Kulish, S. M.; Гоцуля, Андрій Сергійович; Куліш, Сергій Миколайович; Гоцуля, А. С.; Кулиш, С. Н. (Запорізький державний медичний університет, 2020)
Nitrogen-containing heterocyclic compounds play an important role in the modern pharmaceutical industry. This is due to their significant biological potential. 1,2,4-Triazole and pyrazole are known pharmacophores that are responsible for the formation of a wide range of activities. The construction of the target molecule using 1,2,4-triazole and pyrazole is also interesting in terms of the availability of starting reagents and the simplicity of chemical transformations. The combination of these heterocycles in one molecule allows increasing its opportunities of participation in various biological processes. The aim of the research was to examine the conditions for obtaining S-alkylderivatives of 5-(5-methylpyrazole)-4-ethyl-1,2,4-triazole-3- thiol and to investigate these compounds’ properties. Materials and methods. The first phase of the research involved the use of diethyloxalate, acetone and sodium methylate as starting substances for the synthesis of the intermediate. The obtained methyl 2,4-dioxopentanoate in the following step was converted into 5-methylpyrazole-3-carbohydrazide with the double amount of hydrazine hydrate. The subsequent modification of the molecule implied a stepwise use of the reactions of nucleophilic addition of ethyl isothiocyanate and alkaline cyclization. Thus, the obtained 5-(5-methylpyrazole)-4-ethyl-1,2,4-triazole-3-thiol became subject to an alkylation process. To establish the composition and identify the structure of the isolated substances, 1H NMR and infrared spectra were recorded, as well as qualitative and quantitative indicators of the elemental composition of the synthesized structures were obtained. The individual nature of the presence of substances and the degree of their purity were determined using high performance liquid chromatography with two types of detection: diode-matrix and mass spectrometric. Results. The synthesis of alkylderivatives of 5-(5-methylpyrazole)-4-ethyl-1,2,4-triazole-3-thiol was carried out and the optimal conditions for the process of obtaining these substances were determined. The structure of the products of chemical transformation is confirmed and the results of the study of its physical properties are recorded. The results of docking studies allowed to confirm the prospects of the chosen direction of synthetic transformations, which ultimately allowed to determine the biological potential of the obtained compounds. The model enzymes were kinase of the anaplastic lymphoma (code 2XP2), 14-alpha demethylase of the lanosterol (code 3LD6) and cyclooxygenase-1 (code 3N8Y), information on which was obtained from the Protein Structures Database (PDB). Conclusions. Molecular docking resulted in obtaining data that form a concept of a certain level of probability of synthesized compounds’ influence on the activity of these enzyme structures. Нітрогеновмісні гетероциклічні сполуки відіграють важливу роль у сучасній фармацевтичній галузі. Це пов’язано зі значущим біологічним потенціалом цих сполук. 1,2,4-Тріазол і піразол – відомі фармакофори, що відповідають за формування широкого спектра активностей. Конструювання цільової молекули з використанням 1,2,4-тріазолу та піразолу є також цікавим із погляду доступності вихідних реагентів і простоти хімічних перетворень. Поєднання цих гетероциклів в одній молекулі дає змогу збільшити можливість участі в різноманітних біологічних процесах. Мета роботи – дослідження умов одержання S-алкілпохідних 5-(5-метилпіразол)-4-етил-1,2,4-тріазол-3-тіолу та вивчення властивостей цих сполук. Матеріали та методи. Початковий етап роботи передбачав використання діетилоксалату, ацетону та натрій метилату як вихідних речовин для синтезу проміжного продукту хімічного перетворення. Одержаний метил 2,4-діоксопентаноат на наступному етапі застосований у процесі перетворення у 5-метилпіразол-3-карбогідразид за участю подвійної кількості гідразин гідрату. Наступна модифікація молекули полягала в поетапному використанні реакцій нуклеофільного приєднання етилізотіоціанату та лужної гетероциклізації. Сформований так 5-(5-метилпіразол)-4-етил-1,2,4-тріазол-3-тіол піддавали процесу алкілування. Для встановлення складу та ідентифікації структури виділених речовин записані 1Н ЯМР та інфрачервоні спектри, а також одержані якісні та кількісні показники елементного складу синтезованих структур. Індивідуальний характер наявності речовин і ступінь їхньої чистоти визначені з використанням високоефективної рідинної хроматографії з двома видами детекції: діодно-матричної та мас-спектрометричної. Результати. Здійснили синтез алкілпохідних 5-(5-метилпіразол)-4-етил-1,2,4-тріазол-3-тіолу та визначили оптимальні умови процесу одержання цих речовин. Підтверджена будова продуктів хімічного перетворення та зафіксовані результати дослідження фізичних властивостей. Результати докінгових досліджень дали змогу підтвердити перспективність обраного напряму синтетичних перетворень, що врешті дало змогу визначитися з біологічним потенціалом одержаних сполук. Модельні ферменти – анапластичної лімфоми кіназа (код 2XP2), 14-альфа деметилаза ланостеролу (код 3LD6) та циклооксигеназа-1 (код 3N8Y), інформацію щодо яких використано з бази Банку даних білкових структур (РDB). Висновки. У результаті молекулярного докінгу отримали відомості, що формують уявлення про певний рівень імовірності впливу синтезованих сполук на активність названих ферментних структур. Нитрогенсодержащие гетероциклические соединения играют важную роль в современной фармацевтической отрасли. Это связано со значительным биологическим потенциалом указанных соединений. 1,2,4-Триазол и пиразол – известные фармакофоры, которые отвечают за формирование широкого спектра активностей. Конструирование целевой молекулы с использованием 1,2,4-триазола и пиразола интересно с точки зрения доступности исходных реагентов и простоты химических превращений. Совмещение этих гетероциклов в одной молекуле позволяет увеличить возможность участия в разнообразных биологических процессах. Цель работы – исследование условий получения S-алкилпроизводных 5-(5-метилпиразол)-4-этил-1,2,4-триазол-3-тиола и изучение свойств указанных веществ. Материалы и методы. Начальный этап работы предусматривал использование диэтилоксалата, ацетона и натрий метилата как исходных веществ для постановки синтеза промежуточного продукта химического преобразования. Полученный метил 2,4-диоксопентаноат на следующем этапе применен в процессе преобразования в 5-метилпиразол-3-карбогидразид при участии двойного количества гидразин гидрата. Последующая модификация молекулы предусматривала использование этилизотиоцианата и щелочную гетероциклизацию. Сформированный таким образом 5-(5-метилпиразол)-4-этил-1,2,4-триазол-3-тиол подвергали процессу алкилирования. Для установления состава и идентификации структуры выделенных веществ записаны 1Н ЯМР и инфракрасные спектры, а также получены качественные и количественные показатели элементного состава синтезированных структур. Индивидуальный характер присутствия веществ и степень их чистоты определены с использованием высокоэффективной жидкостной хроматографии с двумя видами детекции: диодно-матричной и масс-спектрометрической. Результаты. Проведен синтез алкилпроизводных 5-(5-метилпиразол)-4-этил-1,2,4-триазол-3-тиола и определены оптимальные условия процесса получения указанных веществ. Подтверждено строение продуктов химического преобразования, зафиксированы результаты исследования физических свойств. Результаты докинговых исследований позволяют подтвердить перспективность выбранного направления синтетических преобразований, что дало возможность определиться с биологическим потенциалом полученных веществ. Модельные ферменты: анапластической лимфомы киназа (код 2XP2), 14-альфа деметилаза ланостерола (код 3LD6) и циклооксигеназа-1 (код 3N8Y), информация о которых использована из базы Банка данных белковых структур (PDB). Выводы. В результате молекулярного докинга получены данные, которые формируют представление про определенный уровень вероятности влияния синтезированных соединений на активность указанных ферментных структур.
Синтез і властивості деяких піразолпохідних 1,2,4-тріазол-3-тіолу
Синтез и свойства некоторых пиразолпроизводных 1,2,4-триазол-3-тиола
Гоцуля А. С. - ORCID ID: 0000-0001-9696-221X
Keywords: 5-methylpyrazole; 1,2,4-triazole; physical-chemical properties; molecular docking; 1,2,4-тріазол; піразол; фізико-хімічні властивості; молекулярний докінг; 5-метилпиразол